HYPERPARAMETER TUNING ON RANDOM FOREST FOR DIAGNOSE COVID-19 - Anna Baita; Inggar Adi Prasetyo; Nuri Cahyono (JIKO (Jurnal Informatika dan Komputer), 2023)
Diagnosis of Covid using the RT-PCR (Reverse Transcription Polymerase Chain Reaction) test requires high costs and takes a long time. For this reason, another method is needed that can be used to diagnose Covid-19 quickly and accurately. Random Forest is one of the popular classification algorithms for making predictive models. Random forest involves many hyperparameters that control the structure of each tree, the forest, and its randomness. Random Forest is a method which very sensitive to hyperparameter values, as their prediction accuracy can increase significantly when optimized hyperparameters are predefined and then adjusted according to the procedure. The purpose of doing hyperparameter tuning on the random forest algorithm is to increase accuracy in the diagnosis of covid-19. Searching for optimal values of hyperparameters is done by the Grid Search method and Random Search. The result explains that the Random Forest can be used to diagnose Covid-19 with an accuracy of 94%, and with hyperparameter tuning, it can increase the accuracy of the random forest by 2%.